Tingkat Kewirausahaan Dan Kesuksesan Pada Usaha Kecil Menengah (UKM) - rahmawan, reza ardiansyah (LPPM Universitas Multi Data Palembang, 2024)
The purpose of this paper is to determine the level or characteristics of entrepreneurship to achievesuccess in Small and Medium Enterprises (SMEs). SMEs play a role in providing employment and equity of income through business opportunities. Problems of SMEs on the difficulty of access to markets, information aid, finan-cial aid, and capital constraints. Facing such problems requires a strategy to achieve the success of Small and Medium Enterprises (SMEs) by improving the characteristics of entrepreneurs, characteristics of SMEs, and busi-ness performance.